Intersectionality in Social Justice: Unpacking the Complexity of Oppression - Suyahman, Suyahman; Karimullah, Suud Sarim; Syahril, Muh. Akbar Fhad (Universitas Negeri Gorontalo, 2025)
This study aims to understand, explain, and address the complexities of oppression in a multicultural and multiethnic society such as ASEAN. This study uses a law-based methodological approach that integrates intersectionality, postcolonial, feminist, critical race, and queer theories concerning international legal instruments. Based on the results of the study, mapping the landscape of intersectionality in ASEAN reveals how the interaction of gender, race, class, religion, and sexual orientation creates multiple discriminations, such as those experienced by female migrant workers, the LGBTQ+ community, and religious and ethnic minorities, who are often marginalised in legal systems and public policies. While international instruments demand protection without discrimination, inconsistent implementation of laws in ASEAN exacerbates existing structural injustices. Therefore, a transformative strategy for social justice in ASEAN requires a rights-based approach that focuses on empowering vulnerable groups, their active participation in decision-making processes, and legal reforms that integrate principles of intersectionality to ensure equitable access to justice. This approach can only succeed if ASEAN countries align domestic policies with international standards, strengthen inclusive legal systems, and empower regional mechanisms such as the ASEAN Intergovernmental Commission on Human Rights (AICHR) to more effectively uphold human rights in the region.